Dysfunction of Synaptic Vesicle Endocytosis in Parkinson’s Disease - Zou, Li; Tian, Ye; Zhang, Zhentao (Frontiers in Integrative Neuroscience, 2021)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder after Alzheimer’s disease. It is a chronic and progressive disorder estimated to affect at least 4 million people worldwide. Although the etiology of PD remains unclear, it has been found that the dysfunction of synaptic vesicle endocytosis (SVE) in neural terminal happens before the loss of dopaminergic neurons. Recently, accumulating evidence reveals that the PD-linked synaptic genes, including DNAJC6, SYNJ1 and SH3GL2, significantly contribute to the disruptions of SVE, which is vital for the pathogenesis of PD. In addition, the proteins encoded by other PD-associated genes such as SNCA, LRRK2, PRKN and DJ-1 also play key roles in the regulation of SVE. Here we present the facts about SVE-related genes and discussed their potential relevance to the pathogenesis of PD.